Chronic Stress in Vocational and Intimate Partner Domains as Predictors of Depressive Symptoms After Breast Cancer Diagnosis. Issue 4 (20th June 2018) - Stinesen Kollberg, Karin; Wiley, Joshua F; Ross, Kharah M; Jorge-Miller, Alexandra; Hammen, Constance; Weihs, Karen L; Stanton, Annette L
Abstract: Background: After cancer diagnosis, depressive symptoms are elevated on average and decline over time, but substantial variability is apparent. Few studies have examined to what extent chronic stress in distinct life domains affects depressive symptoms. Purpose: Chronic stress in vocational and intimate partner life domains, and their interaction, were tested as predictors of depressive symptoms after breast cancer diagnosis. Methods: Women ( N = 460) completed validated interviews regarding chronic stress in specific life domains shortly after diagnosis and a measure of depressive symptoms every 6 weeks for 6 months. Results: In latent growth curve modeling analyses, greater chronic stress in work ( b = 2.90; p < .001) and intimate partner domains ( b = 1.38, p = .02) was associated with higher depressive symptoms at study entry (intercept), and greater work stress predicted faster recovery from depressive symptoms over time ( b = –0.10; p = .01). The two domains of chronic stress also interacted significantly on depressive symptoms at study entry ( b = –1.54; p < .02) and over time ( b = 0.14; p < .001). Greater work stress was associated with higher depressive symptoms at study entry regardless of intimate partner stress, but greater intimate partner stress was associated with higher depressive symptoms when work stress was low. The decline over 6 months in initially elevated depressive symptoms predicted by high work stress was significantly steeper when intimate partner stress was low. Conclusions: Targeting interventions to recently diagnosed breast cancer patients living with chronically stressful vocational and intimate partner life circumstances could be worthwhile. Abstract : Chronic stress in vocational and intimate partner domains interacted to predict depressive symptoms in women recently diagnosed with breast cancer.